2017
DOI: 10.1016/j.tibs.2017.05.005
|View full text |Cite
|
Sign up to set email alerts
|

A Puzzle of Life: Crafting Ribosomal Subunits

Abstract: The biogenesis of eukaryotic ribosomes is a complicated process during which the transcription, modification, folding, and processing of the rRNA is coupled with the ordered assembly of $80 ribosomal proteins (r-proteins). Ribosome synthesis is catalyzed and coordinated by more than 200 biogenesis factors as the preribosomal subunits acquire maturity on their path from the nucleolus to the cytoplasm. Several biogenesis factors also interconnect the progression of ribosome assembly with quality control of impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
127
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(143 citation statements)
references
References 113 publications
1
127
0
3
Order By: Relevance
“…Ribosome assembly is a highly regulated process, involving the proper folding and processing of 4 rRNAs, as well as binding of 79 ribosomal proteins (r-proteins). Assembly is facilitated by over 200 transiently binding assembly factors that promote assembly and quality control, and prevent immature ribosomes from initiating translation prematurely (Kressler et al, 2017;Pena et al, 2017;Warner, 1999;Woolford and Baserga, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Ribosome assembly is a highly regulated process, involving the proper folding and processing of 4 rRNAs, as well as binding of 79 ribosomal proteins (r-proteins). Assembly is facilitated by over 200 transiently binding assembly factors that promote assembly and quality control, and prevent immature ribosomes from initiating translation prematurely (Kressler et al, 2017;Pena et al, 2017;Warner, 1999;Woolford and Baserga, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Mammalian ribosomes are nucleoprotein complexes comprised of a large (60S) subunit and a small (40S) subunit that carry out the fundamental process of translation. The mature ribosome contains four ribosomal RNAs (rRNAs) and almost 80 proteins and the complex process of ribosome biogenesis involves over 200 trans-acting factors (reviewed in (Kressler, Hurt, & Baßler, 2017)). Transcription of rRNA precursors from tandem repeats of ribosomal DNA (rDNA) initiates ribosome biogenesis and a complex sequence of events including sequential splicing and recruitment of rRNA-associated proteins ensues.…”
Section: Introductionmentioning
confidence: 99%
“…NOP2 is not required for preimplantation development 5-Methylcytosine (m5C) is a common RNA modification that takes place in a variety of RNA species, including rRNAs. Indeed, a recent study confirmed the presence of m5C in human rRNAs, although its biological role remains unclear.…”
Section: Methyltransferase Activity Ofmentioning
confidence: 99%
“…A functional ribosome is a delicate molecular machine composed of 60S large subunit and 40S small subunit, each of them built from ribosome RNAs (rRNAs) and numerous ribosome proteins. 5,6 Ribosome biogenesis consists of a series of highly coordinated and energy demanding processes, involving a large number of factors and pathways. 7 It starts in the nucleolus, where rRNAs were transcribed by RNA polymerase I (RNA Pol I).…”
Section: Introductionmentioning
confidence: 99%